Art as a protagonist of popular communication in a cultural event: : the Book Fair in Minas do Leão (Revista Internacional de Folkcomunicação, 2023)
The article aims to identify specific communicational traits of a population of a small town, during an already traditional cultural event, the 16th Book Fair in the city of Minas do Leão, in the interior of Rio Grande do Sul, based on the precepts of the theory from Folkcomunicação, by Luiz Beltrão. The methodology used came from ethnography, with field study, participant observation and documentary and bibliographic study. The Fair honored book authors, born in Minas do Leão, with various artistic activities. Among the findings, from the point of view of folkcommunication, it was found that the population found an artistic way to communicate and express themselves, namely: exhibition of drawings, face painting, presentation of schoolwork, chat with authors of books, Marching Band and plays.